The Fas/Fas Ligand Death Receptor Pathway Contributes to Phenylalanine-Induced Apoptosis in Cortical Neurons - Huang, Xiaodong (Public Library of Science, 2013)
Phenylketonuria (PKU), an autosomal recessive disorder of amino acid metabolism caused by mutations in the phenylalanine hydroxylase (PAH) gene, leads to childhood mental retardation by exposing neurons to cytotoxic levels of phenylalanine (Phe). A recent study showed that the mitochondria-mediated (intrinsic) apoptotic pathway is involved in Phe-induced apoptosis in cultured cortical neurons, but it is not known if the death receptor (extrinsic) apoptotic pathway and endoplasmic reticulum (ER) stress-associated apoptosis also contribute to neurodegeneration in PKU. To answer this question, we used specific inhibitors to block each apoptotic pathway in cortical neurons under neurotoxic levels of Phe. The caspase-8 inhibitor Z-IETD-FMK strongly attenuated apoptosis in Phe-treated neurons (0.9 mM, 18 h), suggesting involvement of the Fas receptor (FasR)-mediated cell death receptor pathway in Phe toxicity. In addition, Phe significantly increased cell surface Fas expression and formation of the Fas/FasL complex. Blocking Fas/FasL signaling using an anti-Fas antibody markedly inhibited apoptosis caused by Phe. In contrast, blocking the ER stress-induced cell death pathway with salubrinal had no effect on apoptosis in Phe-treated cortical neurons. These experiments demonstrate that the Fas death receptor pathway contributes to Phe-induced apoptosis and suggest that inhibition of the death receptor pathway may be a novel target for neuroprotection in PKU patients.